2023
DOI: 10.1186/s40708-023-00193-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing biofeedback-driven self-guided virtual reality exposure therapy through arousal detection from multimodal data using machine learning

Abstract: Virtual reality exposure therapy (VRET) is a novel intervention technique that allows individuals to experience anxiety-evoking stimuli in a safe environment, recognise specific triggers and gradually increase their exposure to perceived threats. Public-speaking anxiety (PSA) is a prevalent form of social anxiety, characterised by stressful arousal and anxiety generated when presenting to an audience. In self-guided VRET, participants can gradually increase their tolerance to exposure and reduce anxiety-induce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…This would allow comparing performance under stress between individuals. Another application may be in specific forms of biofeedback, e.g., adapting anxiety-evoking stimuli in virtual reality to appropriate levels in exposure therapy (Repetto et al, 2009;Brouwer et al, 2011;Rahman et al, 2023). While our study showed that we can generalize models across tasks by training models using data from different tasks, it is advisable to, whenever possible, stay within context, since this will result in better performance.…”
Section: Discussionmentioning
confidence: 80%
“…This would allow comparing performance under stress between individuals. Another application may be in specific forms of biofeedback, e.g., adapting anxiety-evoking stimuli in virtual reality to appropriate levels in exposure therapy (Repetto et al, 2009;Brouwer et al, 2011;Rahman et al, 2023). While our study showed that we can generalize models across tasks by training models using data from different tasks, it is advisable to, whenever possible, stay within context, since this will result in better performance.…”
Section: Discussionmentioning
confidence: 80%
“…For the calculation of positioning loss, CIoU (Complete IoU) Loss is used in this paper instead of MSE [14]. The advantage of this kind of loss function is that it not only takes into account the influence of the overlapping area between the predicted boundary frames on the loss calculation but also takes into account the influence of the center point distance and aspect ratio.…”
Section: Loss Functionmentioning
confidence: 99%
“…Alkevicius et al trained a model for anxiety level recognition using physiological signals such as BVP, GSR, and skin temperature [47]. A study by Rahman et al also implemented a biofeedback framework to identify anxiety levels in terms of the heart rate and brain laterality index from acquired multimodal data [48]. The final results prove the validity and accuracy of these two models.…”
Section: Effectiveness Of Vr Interventions and The Relationship Betwe...mentioning
confidence: 99%